A comprehensive study on the improvement of oxidation stability and NOx emission levels by antioxidant addition to biodiesel blends in a light-duty diesel engine. Issue 27 (26th February 2016) - Rashed, M. M.; Masjuki, H. H.; Kalam, M. A.; Alabdulkarem, Abdullah; Imdadul, H. K.; Rashedul, H. K.; Shahin, M. M.; Habibullah, M.
Abstract : Moringa oleifera oil, a non-edible biodiesel feedstock with high unsaturated fatty acid content, was used in this study. Abstract : Moringa oleifera oil, a non-edible biodiesel feedstock with high unsaturated fatty acid content, was used in this study. MB20 (20% Moringa oil methyl ester and 80% diesel fuel blend) was mixed with three antioxidants, namely, N, N ′-diphenyl-1, 4-phenylenediamine (DPPD), N -phenyl-1, 4-phenylenediamine (NPPD) and 2-ethylhexyl nitrate (EHN), at a concentration of 1000 ppm. The effects of these antioxidants on the oxidation stability of biodiesel as well as on the exhaust emission and performance of a single-cylinder diesel engine were analysed. After the Rancimat test, oxidation stability was enhanced by the antioxidants in the order of DPPD > NPPD > EHN. Results also showed that DPPD-, NPPD- and EHN-treated blends reduced NO x emissions within 5.9–8.80% compared with those in the untreated blend because of suppressed free radical formation. Antioxidant-treated blends contained high amounts of carbon monoxide and hydrocarbon and showed improved smoke opacity, thereby indicating that emissions were below the diesel fuel emission levels. Results demonstrated that antioxidant addition to MB20 improves engine performance characteristics. This study shows that MB20 blends with antioxidants can be used in diesel engines without any modification.